Amelioration of cobalt oxide nanoparticles induced genomic and mitochondrial DNA damage and oxidative stress by omega-3 co-administration in mice. Issue 4 (2nd October 2018) - Mohamed, Hanan R. H.; Hussien, Nahed A.
ABSTRACT: Increased human exposure to cobalt oxide nanoparticles (CoO-NPs) because of their widespread use in many industrial and medical applications makes the study of genotoxicity and mutagenicity necessary. Therefore, this study was conducted to assess the genomic and mitochondrial DNA damage induction by CoO-NPs and the possible protective role of omega-3 in mice. The simultaneous administration of omega-3 significantly reduced DNA damage caused by CoO-NPs, which was evaluated by restoring the normal intact appearance of genomic DNA running on the agarose gel and normalizing fractionated DNA. The elevated malondialdehye (MDA) level and the reduced catalase (CAT) and glutathione peroxidase (Gpx) activities by CoO-NPs oral administration were normalized by omega-3 co-administration. Moreover, the omega-3 co-administration reduced the incidence of mutations induced by CoO-NPs in mitochondrial D-loop from 67% to 33%. We concluded that genomic and mitochondrial DNA damage and oxidative stress caused by CoO-NPs was mitigated by omega-3 co-administration.